JUDGING JEHOVAH'S WITNESSES : Religious Persecution and the Dawn of the Rights Revolution - Peters, Shawn Francis, 1966- (Book collections on Project MUSE., 2000)
"One of the worst outbreaks of religious persecution in U.S. history occured during World War II when Jehovah's Witnesses were intimidated, beaten, and even imprisoned for refusing to salute the flag or serve in the armed forces." "Determined to claim their First Amendment rights, Jehovah's Witnesses waged a tenacious legal campaign that led to twenty-three Supreme Court rulings between 1938 and 1946. Now Shawn Peters has written the first complete account of the personalities, events, and institutions behind those cases, showing that they were more than vindication for unpopular beliefs - they were also a turning point in the nation's constitutional commitment to individual rights."--Jacket.